Standardization parameters of leaf and stem bark extracts of Acronychia pedunculata (L.) grown in Sri Lanka: Hapuarachchi S. D., Ukwattage M. I., Kodithuwakku N. D., Silva P. D. S. A., Perera P. K. (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
Acronychia pedunculata (L.) (Ankenda) under family RUTACEAE is widely used in Traditional medicine system. The present study was aimed at the development of quality control parameters for identification and authentication of A. pedunculata. Hence, standardization is important in maintaining the purity, quality, safety and efficacy of Ayurveda formulations. Phytochemical, physico-chemical parameters and HPTLC fingerprints of methanol extracts of leaves and stem barks were determined as tools for quality standards. Preliminary phytochemical analysis revealed the presence of carbohydrates, reducing sugars, tannins, saponins, alkaloids, flavonoids, anthranol glycosides, phenols, terpenoids and proteins in both leaf and stem bark extracts. Under physico-chemical parameters; total ash, acid insoluble ash, water soluble ash, loss on drying and extractability in methanol for A. pedunculata leaves were 40.38% w/w, 12.64% w/w, 34.42% w/w, 21.80% w/w and 17.84% w/w respectively. Total ash, acid insoluble ash, water soluble ash content, loss on drying and extractability in methanol for A. pedunculata stem barks were 20.42% w/w, 8.35% w/w, 25.56% w/w, 15.67% w/w and 13.42% w/w. HPTLC profile of A. pedunculata leaf extract showed 10 peaks (Rf values; -0.01, 0.11, 0.32, 0.39, 0.43, 0.57, 0.69, 0.77, 0.85, 0.88) whereas, stem bark extract also showed 10 peaks (Rf values; -0.06, 0.02, 0.06, 0.17, 0.34, 0.48, 0.61, 0.71, 0.82, 0.97) for solvent system; n-hexane: ethyl acetate: chloroform in 2: 6: 2 ratio. The above parameters can be considered as a preliminary tool in detection and contrast of raw materials excluding the counterfeit and substandard raw materials in Ayurveda manufacturing. Keywords: Acronychia pedunculata (L.); high performance thin layer chromatography; phytochemical; physico-chemical; standardization 1Department of Ayurveda, Institute of Indigenous Medicine, University of Colombo, Rajagiriya, Sri Lanka. 2Department of Agricultural Engineering, Faculty of Agriculture, University of Ruhuna, Sri Lanka. 3Department of Pharmacy, Faculty of Allied Health Sciences, University of Ruhuna, Sri Lanka. *Correspondence: Hapuarachchi S.D., Department of Ayurveda, Institute of Indigenous Medicine, University of Colombo, Sri Lanka. Email: dr.sdhapuarachchi@iim.cmb.ac.lk